Using interactive Methods in teaching speaking for 7th grade learners - Sobirova Khurshida Rakhmanberganovna; Feruza Makhmanazarova (Zien Journals, 2022)
This article is about the importance of using an interactive method in learning to speak English fluently. The importance of speech ability in the article. Here are some things to look for when selecting yours. The importance of the interactive method lies in the effectiveness of its use in teaching speech skills.
Keywords: Interactive methods; speaking skills; young learners